Recent Advances and Perspective of Nanotechnology-Based Implants for Orthopedic Applications - Chen, Ming-qi (Frontiers in Bioengineering and Biotechnology, 2022)
Bioimplant engineering strives to provide biological replacements for regenerating, retaining, or modifying injured tissues and/or organ function. Modern advanced material technology breakthroughs have aided in diversifying ingredients used in orthopaedic implant applications. As such, nanoparticles may mimic the surface features of real tissues, particularly in terms of wettability, topography, chemistry, and energy. Additionally, the new features of nanoparticles support their usage in enhancing the development of various tissues. The current study establishes the groundwork for nanotechnology-driven biomaterials by elucidating key design issues that affect the success or failure of an orthopaedic implant, its antibacterial/antimicrobial activity, response to cell attachment propagation, and differentiation. The possible use of nanoparticles (in the form of nanosized surface or a usable nanocoating applied to the implant's surface) can solve a number of problems (i.e., bacterial adhesion and corrosion resilience) associated with conventional metallic or non-metallic implants, particularly when implant techniques are optimised. Orthopaedic biomaterials' prospects (i.e., pores architectures, 3D implants, and smart biomaterials) are intriguing in achieving desired implant characteristics and structure exhibiting stimuli-responsive attitude. The primary barriers to commercialization of nanotechnology-based composites are ultimately discussed, therefore assisting in overcoming the constraints in relation to certain pre-existing orthopaedic biomaterials, critical factors such as quality, implant life, treatment cost, and pain alleviation.